TOXICITY OF SOME MARINE SNAILS RESPONSIBLE FOR RECENT FOOD POISONINGS IN VIETNAM - Ha, Dao Viet; Sato, Shigeru (Vietnam Journal of Marine Science and Technology, 2012)
During the years of 2006 - 2007, about five food poisoning cases with fatalities caused by marine snails reported in coastal areas of Vietnam. From stock over of poisoning materials from three out of five cases, causative species were identified as Nassarius papillosus, Nassasius (Alectrion) glans glans, N. (Zeuxis) comptus and Natica (Natica) fasciata. These species also caused poisonings in several countries such as Japan, the Philippines, Brunei and Taiwan. High level of tetrodotoxin was found in the specimens of N. papillosus as the causative component for food poisoning with three patients including two deaths on October 17, 2006 in Quang Ngai province. In contrast, no tetrodotoxin was detected in three other snail species which were eaten at the poisonings on December 17, 2007 in Ninh Thuan province and December 27, 2007 in Binh Thuan province. Although the origin of tetrodotoxin in marine snails has not been clarified yet, it is urgently necessary to warn potential risks from marine snails to public as some of them may become suddenly toxic with unknown mechanism. Tóm tắt: Có ít nhất 5 vụ ngộ độc thực phẩm do ăn ốc biển được ghi nhận tại các vùng ven biển Việt Nam trong các năm 2006-2007. Mẫu vật ốc biển còn sót lại của 3 trong số 5 vụ ngộ độc này được xác định thuộc các loài Nassarius papillosus, Nassasius (Alectrion) glans glans, N. (Zeuxis) comptus và Natica (Natica) fasciata. Đây cũng là những loài gây ra những vụ ngộ độc tương tự ở một số Quốc gia khác như Nhật Bản, Phi-lip-pin, Brunây và Đài Loan. Bằng phương pháp sắc ký lỏng hiệu năng cao (HPLC), đã xác định được hàm lượng khá cao độc tố tetrodotoxin (TTX) trong mẫu vật của loài N. papillosus gây ra vụ ngộ độc cho 3 nạn nhân (2 tử vong) ngày 17 - 10 - 2006 tại tỉnh Quảng Ngãi. Ngược lại, không tìm thấy sự có mặt của độc tố TTX trong 3 loài ốc biển nghi ngờ gây ra 2 vụ ngộ độc khác vào 17 - 12 - 2007 tại Ninh Thuận và 27 - 12 - 2007 tại Bình Thuận. Mặc dù nguồn gốc của độc tố TTX trong ốc biển vẫn còn chưa được biết đến, nhưng một số loài ốc biển có thể trở nên độc một cách bất thường vào một thời điểm nhất định nào đó, do vậy cần thiết phải có cảnh báo về nguy cơ ngộ độc từ những loài sinh vật này.